Does "Information" Provide a Compelling Framework for a Theory of Natural Selection? Grounds for Caution. Issue 1 (January 2014) - Sarkar, Sahotra
Abstract : Frank has recently argued for an information-theoretic interpretation of natural selection. This interpretation is based on the identification of a measure related to the Malthusian parameter (for population change) with the Jeffreys divergence between the present allelic distribution of the population and that distribution in the next generation. It is pointed out in this analysis that this identification only holds if the mean fitness of the population is a constant, that is, there is no selection. This problem is used to argue for the superiority of the standard dynamical interpretation of natural selection over its information-theoretic counterpart.